2013
DOI: 10.1021/ja311503q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag Nanocubes 18–32 nm in Edge Length: The Effects of Polyol on Reduction Kinetics, Size Control, and Reproducibility

Abstract: This article describes a robust method for the facile synthesis of small Ag nanocubes with edge lengths controlled in the range of 18–32 nm. The success of this new method relies on the substitution of ethylene glycol (EG) -- the solvent most commonly used in a polyol synthesis -- with diethylene glycol (DEG). Owing to the increase in hydrocarbon chain length, DEG possesses a higher viscosity and a lower reducing power relative to EG. As a result, we were able to achieve a nucleation burst in the early stage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
268
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(281 citation statements)
references
References 50 publications
9
268
1
3
Order By: Relevance
“…1,2 Nevertheless, it has also been reported that the capping agents used in colloidal synthesis are not merely stabilisers but also effective additives which modify the final NPs morphology features, not only in terms of NPs size and shape, [3][4][5][6] but also of electronic properties. [7][8][9] Thus, despite this necessity, the impact of these molecules once the metal NPs are synthesised is a difficult issue, as it will affect the catalytic behaviour of metal-based catalytic systems by modifying either the NPs physicochemical properties or their accessibility by creating a physical barrier that hinders the access of reactants to the surface NPs catalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nevertheless, it has also been reported that the capping agents used in colloidal synthesis are not merely stabilisers but also effective additives which modify the final NPs morphology features, not only in terms of NPs size and shape, [3][4][5][6] but also of electronic properties. [7][8][9] Thus, despite this necessity, the impact of these molecules once the metal NPs are synthesised is a difficult issue, as it will affect the catalytic behaviour of metal-based catalytic systems by modifying either the NPs physicochemical properties or their accessibility by creating a physical barrier that hinders the access of reactants to the surface NPs catalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
“…stated that those Ag nanocubes with controlled lengths below 30 nm only are prepared by using DEG as solvent (12). The alternative use of EG or polyols with longer hydrocarbon chains (TEG or TREG) only led to the formation of twinned particles with irregular shapes.…”
Section: Preparation and Characterization Of Sb-and Cr-containing Tiomentioning
confidence: 99%
“…The synthesis of metallic nanoparticles has been improved to the extent that control over their geometrical parameters and distribution can be achieved [3][4][5][6]. The size, morphology, surrounding dielectric environment and metallic type determine the plasmonic frequencies [7] and the relative intensities of the LSPR modes [8].…”
Section: Introductionmentioning
confidence: 99%